Negative electrode material for sodium ion battery and preparation method thereof, sodium ion battery
Through secondary carbonization treatment of anthracite, the anthracite is cracked in the NH3/Ar atmosphere to prepare a hard carbon anode material with a high specific surface area, which solves the problem of low efficiency of the hard carbon anode material of sodium ion battery for the first time, improves the electrochemical performance and energy density of the battery, and is suitable for industrial production.
Patent Information
- Application Number
- CN202311200715.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-18
- Publication Date
- 2025-09-02
- Estimated Expiration
- 2043-09-18
AI Technical Summary
The hard carbon anode material of existing sodium ion batteries has low efficiency for the first time, limiting the improvement of its electrochemical performance.
Secondary carbonization is used to treat anthracite, and the anthracite is cracked in an NH3/Ar atmosphere. By introducing defects and adjusting the carbon layer spacing, a hard carbon anode material with a high specific surface area is prepared.
It improves the Coulomb efficiency of hard carbon anode material and the energy density of sodium ion batteries, simplifies the preparation process and reduces energy consumption, and is suitable for industrial production.
Smart Images

Figure CN117069105B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a negative electrode material for a sodium ion battery and a preparation method thereof, and a sodium ion battery. Background Art
[0002] With the gradual depletion of fossil fuels, new energy sources such as wind, solar, and tidal power have attracted widespread attention worldwide. These new energy sources are characterized by low utilization rates, intermittent operation, and difficulty connecting to the grid. To enable the large-scale deployment of these clean, renewable energy sources, the development of energy storage devices is imperative. Lithium-ion batteries, with their excellent electrochemical properties, are currently the most commercially successful battery, widely used in mobile phones, laptops, and electric vehicles. However, global lithium reserves are limited and unevenly distributed, making lithium-ion batteries prohibitively expensive for large-scale energy storage, far from meeting the needs of large-scale renewable energy deployment. Lithium and sodium, adjacent elements in the same main group of the periodic table, possess very similar physical and chemical properties. Furthermore, sodium-ion batteries offer abundant sodium resources, low cost, environmental friendliness, and a uniform distribution in the Earth's crust, as well as a very similar energy storage mechanism. Therefore, sodium-ion batteries are considered the most promising alternative to lithium-ion batteries for large-scale energy storage systems. However, sodium-ion batteries also suffer from inherent drawbacks such as low capacity. The large radius of sodium ions makes finding a suitable sodium intercalation material challenging. Therefore, it is imperative to develop negative electrode materials with high specific capacity.
[0003] In the past three decades, the development of sodium-ion batteries has been greatly limited by the negative electrode materials. Carbon materials (carbon nanotubes, carbon nanospheres and graphene) are considered to be the most promising sodium-ion negative electrode materials due to their chemical stability, relative abundance and high sodium storage capacity. In particular, hard carbon, due to its large interlayer and a large number of lattice defects, can make more Na + However, hard carbon has a large irreversible capacity, which results in a low first coulombic efficiency.
[0004] In order to optimize and adjust the microstructure and pore structure of hard carbon materials, Chinese patent document CN112645305 A discloses a preparation method of anthracite-based hard carbon material by combining pre-activation pore formation with high-temperature carbonization, which comprises the following steps: (1) grinding and screening: crushing and screening the raw coal to obtain powder of target particle size; (2) pre-activation: mixing the activation gas or activator with the powder, heating the mixture to 700-1000°C at a heating rate of 2-20°C / min under the protection of an inert atmosphere, and keeping the temperature for 1-6 hours to obtain a pre-activated product; (3) carbonization: heating the pre-activated product to 800-1800°C at a heating rate of 2-20°C / min under the protection of an inert atmosphere, and keeping the temperature for 0.5-10 hours to obtain anthracite-based hard carbon material. When hard carbon materials are used as anodes for sodium-ion batteries, the reversible capacity is 254.4 mAh / g at 0.1C (1C = 300 mA / g) (cycles 0-10). The resulting electrochemical performance needs to be improved. Therefore, the search for efficient sodium-ion anode materials is urgent. Summary of the Invention
[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a negative electrode material for a sodium ion battery, a preparation method thereof, and a sodium ion battery, so as to solve the problem of low first coulombic efficiency of existing coal-based hard carbon.
[0006] The technical solutions of the present invention are as follows:
[0007] The present invention provides a method for preparing a negative electrode material for a sodium ion battery, comprising the following steps:
[0008] (1) After the anthracite is de-impurified and crushed to a target particle size, the anthracite is subjected to a first carbonization treatment under an inert atmosphere to obtain a first carbonized product;
[0009] (2) pre-activating the first carbonization product obtained in step (1) under ammonia and an inert atmosphere to obtain a pre-activated product;
[0010] (3) Under an inert atmosphere, the pre-activated product obtained in step (2) is subjected to a second carbonization treatment to obtain a negative electrode material for a sodium ion battery.
[0011] In one specific embodiment, in step (1), the method for removing impurities from the anthracite is: washing the anthracite with acid solution and water in sequence, and obtaining the anthracite from which impurities are removed after drying; the acid solution is hydrochloric acid and / or hydrofluoric acid, the concentration of the hydrochloric acid is 3-7 mol / L, and the mass concentration of the hydrofluoric acid is 8-12 wt%; during the washing process, the mass volume ratio of the anthracite to the acid solution is 4-6:80-120 (g:mL); preferably, the concentration of the hydrochloric acid is 5 mol / L, and the mass concentration of the hydrofluoric acid is 10 wt%.
[0012] The main purpose of anthracite washing is to remove impurities. The washing process can be carried out using hydrochloric acid, hydrofluoric acid and water in sequence.
[0013] In one embodiment, in step (1), the target particle size of the anthracite is 10-100 μm.
[0014] In one embodiment, in step (1), the first carbonization treatment is specifically: heating to 800-1000°C at a heating rate of 3-7°C / min and keeping warm for 1-3 hours; preferably, in step (1), the first carbonization treatment is specifically: heating to 900°C at a heating rate of 5°C / min and keeping warm for 2 hours.
[0015] In one embodiment, in step (2), the volume ratio of ammonia to inert atmosphere is 1:1-1:3, and the gas flow rate of ammonia and inert atmosphere is 100-300 mL / min; preferably, the volume ratio of ammonia to inert atmosphere is 1:1, and the gas flow rate of ammonia and inert atmosphere is 200 mL / min.
[0016] In one embodiment, the inert atmosphere is at least one of argon, helium, neon, krypton, xenon, and radon.
[0017] In the present invention, the inert atmosphere is an atmosphere that does not participate in the reaction, such as argon, helium, neon, krypton, xenon, radon, etc.
[0018] In one embodiment, the pre-activation treatment is specifically: heating to 800-1000°C at a heating rate of 3-7°C / min and keeping warm for 1-3 hours; preferably, the pre-activation treatment is specifically: heating to 900°C at a heating rate of 5°C and keeping warm for 2 hours.
[0019] In one embodiment, in step (3), the second carbonization treatment is specifically: carbonization at 1100-1300°C for 1-3 hours; preferably, in step (3), the second carbonization treatment is specifically: carbonization at 1200°C for 2 hours.
[0020] The present invention also provides a negative electrode material for a sodium ion battery, which is prepared by the above-mentioned preparation method.
[0021] The present invention also provides a sodium ion battery, the negative electrode of which comprises the negative electrode material for a sodium ion battery as claimed in claim 1 or the negative electrode material for a sodium ion battery prepared by the above preparation method.
[0022] Compared with the prior art, the technical solutions of the present invention are as follows:
[0023] 1. This invention utilizes secondary carbonization to prepare coal-based hard carbon. Anthracite is used as the carbon source and cracked in an NH3 / Ar (1:1 (v / v)) atmosphere. A secondary high-temperature carbonization process yields the hard carbon anode material. During the carbonization process, NH3 decomposes into active species such as H, NH, and NH2. These species diffuse into the anthracite, introducing defects, increasing interlayer spacing, and regulating the carbon morphology and microstructure.
[0024] 2. The present invention applies anthracite to the hard carbon negative electrode material of sodium ion batteries by heat treatment, and studies the two parameters of NH3 / Ar (1:1 (v / v)) atmosphere and secondary carbonization temperature. The obtained hard carbon negative electrode has a suitable specific surface area and closed pores, which can improve the coulombic efficiency of the coal-based hard carbon negative electrode, increase the capacity of the electrode material, and thus improve the energy density of the sodium ion battery.
[0025] 3. The preparation method of the present invention requires few raw materials and reagents, the synthesis process conditions are easy to control, the operation is simple, the temperature is low, the energy consumption is low, the yield is high, and it is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a scanning electron microscope image of the sodium ion battery negative electrode material AC-900 prepared in Comparative Example 1;
[0027] Figure 2 This is a scanning electron microscope image of the sodium ion battery negative electrode material N-AC-900 prepared in Comparative Example 2;
[0028] Figure 3 This is a scanning electron microscope image of the sodium ion battery negative electrode material N-AC-1400 prepared in Comparative Example 3;
[0029] Figure 4 This is a scanning electron microscope image of the sodium ion battery negative electrode material N-AC-1200 prepared in Example 1;
[0030] Figure 5 Transmission electron micrographs of the negative electrode materials of Comparative Examples 1-3 and Example 1;
[0031] Figure 6 is the X-ray diffraction pattern of the negative electrode materials prepared in Comparative Examples 1-3 and Example 1;
[0032] Figure 7 is the Raman spectra of the negative electrode materials prepared in Comparative Examples 1-3 and Example 1;
[0033] Figure 8 This is a summary of the Raman data and X-ray diffraction data of the negative electrode materials prepared in Comparative Examples 1-3 and Example 1;
[0034] Figure 9 and Figure 10is the X-ray energy spectrum of the negative electrode materials prepared in Comparative Examples 1-3 and Example 1;
[0035] Figure 11 This is a graph showing the relationship between the nitrogen content and NQ (graphitic nitrogen) content of three negative electrode materials: N-AC-900, N-AC-1200, and N-AC-1400.
[0036] Figure 12 This is the relationship between the oxygen content of the negative electrode material and the second carbonization temperature and the first coulombic efficiency of the electrode;
[0037] Figure 13 1 is a graph showing nitrogen adsorption and desorption curves of the negative electrode materials prepared in Comparative Examples 1-3 and Example 1;
[0038] Figure 14 is a pore size distribution diagram of the negative electrode materials prepared in Comparative Examples 1-3 and Example 1;
[0039] Figure 15 The negative electrode material prepared by the present invention is 0.1Ag -1 Cycling performance diagram under current density;
[0040] Figure 16 This is a rate performance diagram of AC-900, N-AC-900, N-AC-1200 and N-AC-1400 of the present invention. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0042] Comparative Example 1
[0043] (1) washing anthracite with 5 mol / L hydrochloric acid and 10 wt.% hydrofluoric acid to remove impurities, then repeatedly washing with deionized water, and drying at 80°C for 10 h to obtain anthracite free of impurities;
[0044] (2) After the anthracite was ball-milled for 30 min, it was heated to 900 °C at a heating rate of 5 °C / min in an argon atmosphere and kept at this temperature for 2 h to obtain a carbonized product, which was recorded as AC-900.
[0045] Comparative Example 2
[0046] (1) washing anthracite with 5 mol / L hydrochloric acid and 10 wt.% hydrofluoric acid to remove impurities, then repeatedly washing with deionized water, and drying at 80°C for 10 h to obtain anthracite free of impurities;
[0047] (2) After the anthracite was ball-milled for 30 min, it was heated to 900 °C at a heating rate of 5 °C / min under an argon atmosphere and kept at this temperature for 2 h to obtain a carbonized product;
[0048] (3) In an NH3 / Ar (1:1 (v / v)) atmosphere, the carbonized product obtained in step (2) was heated to 900°C at a heating rate of 5°C and kept warm for 2 h to obtain a preactivated product, designated as N-AC-900, wherein the flow rates of NH3 and Ar gases were 200 mL / min.
[0049] Comparative Example 3
[0050] (1) washing anthracite with 5 mol / L hydrochloric acid and 10 wt.% hydrofluoric acid to remove impurities, then repeatedly washing with deionized water, and drying at 80°C for 10 h to obtain anthracite free of impurities;
[0051] (2) After the anthracite was ball-milled for 30 min, it was heated to 900 °C at a heating rate of 5 °C / min under an argon atmosphere and kept at this temperature for 2 h to obtain a carbonized product;
[0052] (3) In an NH3 / Ar (1:1 (v / v)) atmosphere, the carbonized product obtained in step (2) was heated to 900°C at a heating rate of 5°C and kept at that temperature for 2 h to obtain a preactivated product, wherein the flow rate of NH3 and Ar gas was 200 mL / min;
[0053] (4) Under an argon atmosphere, the pre-activated product obtained in step (3) was carbonized at 1400°C for 2 h to obtain a hard carbon negative electrode material, which was recorded as N-AC-1400.
[0054] Example 1
[0055] (1) washing anthracite with 5 mol / L hydrochloric acid and 10 wt.% hydrofluoric acid to remove impurities, then repeatedly washing with deionized water, and drying at 80°C for 10 h to obtain anthracite free of impurities;
[0056] (2) After the anthracite was ball-milled for 30 min, it was heated to 900 °C at a heating rate of 5 °C / min under an argon atmosphere and kept at this temperature for 2 h to obtain a carbonized product;
[0057] (3) In an NH3 / Ar (1:1 (v / v)) atmosphere, the carbonized product obtained in step (2) was heated to 900°C at a heating rate of 5°C and kept at that temperature for 2 h to obtain a preactivated product, wherein the flow rate of NH3 and Ar gas was 200 mL / min;
[0058] (4) Under an argon atmosphere, the pre-activated product obtained in step (3) was carbonized at 1200°C for 2 h to obtain a hard carbon negative electrode material, which was recorded as N-AC-1200.
[0059] The scanning electron microscope images of the negative electrode materials prepared in Comparative Examples 1-3 and Example 1 are as follows: Figures 1-4 As shown in the figure, it can be seen that the surface of anthracite-based hard carbon treated with NH3 is very rough and has traces of etching.
[0060] Transmission electron microscopy of the negative electrode materials prepared from Comparative Examples 1-3 and Example 1 Figure 5 , where (a) represents N-AC-900, (b) represents AC-900, (c) represents N-AC-1200, and (d) represents N-AC-1400; (e), (f), (g), (h), and (i) represent the distribution of C, N, and O in N-AC-1200. It can be seen that nitrogen was successfully introduced into anthracite-based hard carbon via NH3. The carbon interlayer spacings of AC-900, N-AC-900, N-AC-1200, and N-AC-1400 are 0.372nm, 0.414nm, 0.397nm, and 0.385nm, respectively. The carbon interlayer spacing of N-AC-1400 is smaller than that of N-AC-1200, likely due to the reduced nitrogen doping in N-AC-1400 and the disappearance of some micropores, which leads to a narrower carbon interlayer spacing. Excessive carbon interlayer spacing results in a larger irreversible capacity, while a very narrow carbon interlayer spacing is not conducive to the insertion and extraction of sodium ions. Selective area electron diffraction (SAED) patterns of AC-900, N-AC-900, N-AC-1200, and N-AC-1400 show a gradual increase in the clarity of the diffraction rings, confirming the increasing order of the anthracite-based hard carbon structure.
[0061] The negative electrode material image characterization diagrams prepared in Comparative Examples 1-3 and Example 1 are shown in Figure 6-Figure 14 As shown, Figure 6 The X-ray diffraction pattern shows that the broad peaks of AC-900 at approximately 24.70° and 43.14° correspond to the (002) and (101) crystal planes of carbon, respectively. After N doping, the (002) peak position of N-AC-900 shifts to a lower diffraction angle of 24.84°. This shift indicates that N doping can increase the interlayer distance and promote the formation of a more disordered structure, which is consistent with the transmission electron microscopy image. With the increase of heating temperature, the position of the (002) peak shifts to a higher diffraction angle, indicating that the d-spacing (d002) of the carbon layer decreases. Figure 7 This is the Raman spectrum, about 1333cm in the carbon matrix -1 (d-band) and 1597cm -1There are two characteristic peaks at (g band), and the ID / IG values of AC-900, N-AC-900, N-AC-1200 and N-AC-1400 are 1.68, 3.46, 2.68 and 2.52, respectively. The carbon disordered structure caused by NH3 at high temperature further confirms the increase of ID / IG value; Figure 8 This is a summary of Raman data and X-ray diffraction data. Black represents defects. The larger the AD / AG value, the more defects there are. Figure 9 and Figure 10 The full scan spectra of N-AC-900, N-AC-1200 and N-AC-1400 clearly show the peaks of three elements: C, N and O, indicating that nitrogen is doped into anthracite through NH3. Figure 11 This is a relationship diagram of the nitrogen content and NQ (graphitic nitrogen) content of the three negative electrode materials N-AC-900, N-AC-1200 and N-AC-1400. It can be seen that with the increase of the second carbonization temperature, the nitrogen content gradually decreases and the NQ (graphitic nitrogen) content gradually increases; Figure 12 The graph shows the relationship between the oxygen content of the negative electrode material and the second carbonization temperature and the first coulombic efficiency of the electrode, which shows that as the carbonization temperature increases, the oxygen content in the sample decreases and the coulombic efficiency increases; Figure 13 The nitrogen adsorption and desorption curves of the four negative electrode materials show that N-AC-900 (anthracite treated with ammonia) has a larger specific surface area. As the secondary carbonization temperature increases, the specific surface area gradually decreases. Figure 14 The pore size distribution of the four negative electrode materials is shown in Figure 2. AC-900 has a small specific surface area and large pores, which is not conducive to Na + There are a large number of mesopores in N-AC-900, with pore sizes ranging from 2nm to 50nm, accounting for 79.6% of the total pore volume. Large specific surface area and large pores often lead to low CE of the battery. The pore size of N-AC-1200 after secondary carbonization is mostly below 3nm, which is conducive to Na + The reversible storage of sodium ions can be achieved by the secondary carbonization temperature of 1400 °C, which removes more functional groups and heteroatoms and produces more nanovoids, which is beneficial to improving the Coulomb efficiency of the material. However, the higher temperature will make the carbon layer more ordered, which is not conducive to the storage of sodium ions.
[0062] Performance Verification
[0063] The products prepared in Comparative Examples 1-3 and Example 1 were applied to sodium ion batteries. Specifically, the negative electrode material was fully and evenly mixed with the conductive agent Super P and CMC to obtain a slurry. The slurry was then evenly coated on copper foil or aluminum foil, and the sheet was weighed. In a glove box, a metallic sodium sheet was used as the counter electrode, commercial glass fiber was used as the diaphragm, and a 1 mol / L electrolyte (solute: NaClO4, solvent V(EC):V(EMC):V(DMC) volume ratio = 1:1:1) was used. The battery was assembled in the following order: positive electrode shell → electrode sheet → electrolyte → diaphragm → electrolyte → sodium sheet → current collecting steel sheet → shrapnel → negative electrode shell assembly battery, and then the battery was sealed and pressed with a sealing machine. Finally, it was left to stand at room temperature for 12 hours in preparation for testing the electrochemical performance.
[0064] The prepared sodium ion batteries were placed in 0.1Ag -1 The constant current charge and discharge performance test was carried out at a current density of Figure 15 Thanks to the regulation of carbon interlayer spacing and nitrogen doping, the N-AC-1200 electrode exhibits a high capacity of 220 mAh g after 500 cycles. -1 In comparison, the reversible capacities of AC-900, N-AC-900, and N-AC-1400 electrodes after 500 cycles were 120 mAh g -1 , 149mAh g -1 and 185mAh g -1 , showing a lower specific capacity.
[0065] At different current densities, the rate performance of AC-900, N-AC-900, N-AC-1200 and N-AC-1400 is as follows: Figure 16 As shown. At 0.05Ag -1 , 0.1Ag -1 , 0.2Ag -1 , 0.5Ag -1 , 1.0Ag -1 and 0.05Ag -1 At the current density, the capacity of N-AC-1200 electrode is 282 mAh g -1 , 253mAh g -1 , 205mAh g -1 , 182mAh g -1 , 140mAh g -1 and 286mAh g -1 The capacity is significantly higher than that of the other three electrodes at all current densities, indicating that the N-AC-1200 electrode has a + Excellent performance in storage.
[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a negative electrode material for a sodium ion battery, characterized in that: The steps include: (1) After the anthracite is de-impurified and crushed to a target particle size, the anthracite is subjected to a first carbonization treatment under an inert atmosphere to obtain a first carbonized product; (2) pre-activating the first carbonization product obtained in step (1) under ammonia and an inert atmosphere to obtain a pre-activated product; (3) Under an inert atmosphere, the pre-activated product obtained in step (2) is subjected to a second carbonization treatment to obtain a negative electrode material for a sodium ion battery; In step (1), the first carbonization treatment is specifically as follows: heating to 800-1000°C at a heating rate of 3-7°C / min and keeping the temperature for 1-3h; In step (2), the volume ratio of ammonia gas to inert atmosphere is 1:1-1:3, and the gas flow rate of ammonia gas and inert atmosphere is 100-300 mL / min; The pre-activation treatment is specifically as follows: heating to 800-1000°C at a heating rate of 3-7°C / min and keeping warm for 1-3 hours; In step (3), the second carbonization treatment is specifically: carbonization at 1100-1300° C. for 1-3 hours.
2. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, wherein In step (1), the anthracite is removed from the anthracite by washing the anthracite with an acid solution and water in sequence, and drying the anthracite to obtain the removed anthracite; the acid solution is hydrochloric acid and / or hydrofluoric acid, the concentration of the hydrochloric acid is 3-7 mol / L, and the mass concentration of the hydrofluoric acid is 8-12 wt%; during the washing process, the mass volume ratio of the anthracite to the acid solution is 4-6:80-120 (g:mL).
3. The method for preparing a negative electrode material for a sodium ion battery according to claim 2, wherein: The concentration of the hydrochloric acid is 5 mol / L, and the mass concentration of the hydrofluoric acid is 10 wt %.
4. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, wherein In step (1), the target particle size of the anthracite is 10-100 μm.
5. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, wherein: In step (1), the first carbonization treatment is specifically as follows: heating to 900° C. at a heating rate of 5° C. / min and keeping the temperature for 2 h.
6. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, wherein: The volume ratio of ammonia gas to inert atmosphere was 1:1, and the gas flow rates of ammonia gas and inert atmosphere were 200 mL / min.
7. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, wherein: The inert atmosphere is at least one of argon, helium, neon, krypton, xenon, and radon.
8. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, wherein: The pre-activation treatment is specifically as follows: heating to 900°C at a heating rate of 5°C and keeping the temperature for 2 hours.
9. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, wherein: In step (3), the second carbonization treatment is specifically: carbonization at 1200° C. for 2 h.
10. A negative electrode material for a sodium ion battery, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.
11. A sodium ion battery, characterized in that The negative electrode comprises the negative electrode material for a sodium ion battery according to claim 10 or the negative electrode material for a sodium ion battery prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of anthracite-based hard carbon material combining pre-activation pore-forming and high-temperature carbonization
CN112645305A
Coal-based porous sodium ion battery hard carbon negative electrode material and preparation method thereof
CN116715239A